(untitled) (The Pakistan Development Review, 2001)
Turkey has suffered from different economic crises since 1990. However, the February 2001 crisis has been unprecedented in intensity and repercussions. Although many factors, both internal and external, may have contributed to their occurrences, the former owing to their inducing corruption and waste in the economy, seem to have fomented them more than the latter. Although Turkey has been getting transformed into a market economy since 1980, government intervention is still pervasive in its economy. Government still controls Central Bank, owns commercial banks, and operates public enterprises. It has liberalised market, currency, foreign trade and foreign direct investment (FDI), but still operates sectors like energy, sugar and tobacco. Such a level of state intervention had adverse implications for corruption, waste, effective reforms, etc. in the country. Further, since the transformation of the economy could not be accompanied by concomitant structural, legal and institutional reforms in 1990s, resources have constantly been misused over the years. Further still, groups owning bank, media and holding companies jointly have notoriously precipitated domestic financial crisis by stashing away the home deposits in their offshore branches. Finally, supporting agriculture and industry with politically-motivated credit for voting purposes has constantly been aggravating the drain of resources and thereby financial crises of the country. This paper attempts a critical examination of how such factors may have contributed to the occurrence and accentuation of economic crises suffered by Turkey over the last decade.